2019
DOI: 10.1186/s13027-019-0239-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of P.gingivalis in gastrointestinal cancer: a mini review

Abstract: Bacterial infection may be involved in the entire process of tissue carcinogenesis by directly or indirectly affecting the occurrence and development of tumors. Porphyromonas gingivalis (P.gingivalis) is an important pathogen causing periodontitis. Periodontitis may promote the occurrence of various tumors. Gastrointestinal tumors are common malignant tumors with high morbidity, high mortality, and low early diagnosis rate. With the rapid development of molecularbiotechnology, the role of P.gingivalis in diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 90 publications
0
36
0
Order By: Relevance
“…More specifically, exposure to the bacterium Helicobacter Pylori is suggested as a risk factor for pancreatic cancer (14)(15)(16)(17). Data also suggest a positive association between periodontal disease, due to an infection of the periodontal bacterium Porphyromonas gingivalis and Fusobacterium species, and pancreatic cancer risk (8,(18)(19)(20)(21)(22)(23). The microbiota immune modulation promoting cancer pathogenesis has been explained through inflammatory processes in the tumor tissue, however it has also been shown in mice that bacteria not present in the tumorigenic tissue can promote carcinogenesis, nor do they need to cause inflammation in the tumor microenvironment (8,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, exposure to the bacterium Helicobacter Pylori is suggested as a risk factor for pancreatic cancer (14)(15)(16)(17). Data also suggest a positive association between periodontal disease, due to an infection of the periodontal bacterium Porphyromonas gingivalis and Fusobacterium species, and pancreatic cancer risk (8,(18)(19)(20)(21)(22)(23). The microbiota immune modulation promoting cancer pathogenesis has been explained through inflammatory processes in the tumor tissue, however it has also been shown in mice that bacteria not present in the tumorigenic tissue can promote carcinogenesis, nor do they need to cause inflammation in the tumor microenvironment (8,58).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focused on humoral responses to Helicobacter pylori and found contradicting results (14)(15)(16)(17). More recently, periodontal disease, caused by bacterial infections of pathogens such as Porphyromonas gingivalis and Fusobacterium species, has been suggested to play a role in the development and prognosis of pancreatic cancer (18)(19)(20)(21)(22)(23)(24). Furthermore, other responses of the humoral immune system, such as allergic reactions, may present a protective effect for pancreatic cancer diagnosis (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there have been many reports, mainly from Japanese researchers, regarding the effects of preoperative oral and dental health management for prevention of postoperative complications [ 2 , 4 6 ]. Furthermore, some recent literature has shown interesting information about the association between oral microbiota and malignant digestive diseases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is growing evidence associating different mechanistic links between periodontitis and some malignant digestive diseases, as a noteworthy topic [ 8 , 10 ]. It is an important research field in order to provide oral health education to the general public.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the epidemiological evidence implicating P. gingivalis in pancreatic tumorigenesis [ 19 ], the direct effects of this bacterium on PDAC tumor progression have not been investigated, and the mechanisms underlying the P. gingivalis –PDAC link remain unclear. Here, we provide the first evidence that P. gingivalis exerts direct pro-tumorigenic effects on pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%